Defining fatigue from the experiences of patients living with chronic fatigue - Rio, Carielle Joy; Gehling, Gina M.; Blumhorst, Catherine; Ross, Alexander; Saligan, Leorey N. (Frontiers in Medicine, 2024)
Introduction Fatigue is a multidimensional, highly individualized symptom experience perceived by people, regardless of health status. It is the most common complaint among those seeking primary care, yet, despite being a frequently reported symptom, it remains poorly understood. Methods This is an exploratory study utilizing a qualitative descriptive approach that aims to explore the description of fatigue from the personal experiences of 16 participants living with chronic fatigue. Themes were generated from transcripts of in-depth interviews that focused on a central question: “how would you describe your fatigue from your own experience?” Results Analysis of the participants’ interview transcripts revealed three themes. The first theme focused on fatigue as a unique personal experience, which included experiential descriptions or measures of fatigue that the participants used to describe their symptoms. The second theme focused on fatigue as an experience beyond self, which highlighted the consequences of fatigue on interpersonal interactions and the performance of social roles, as well as the potential of utilizing social support to cope with the limitations caused by this condition. The last theme was on living with fatigue, which focused on ways participants attempted to discern their condition and manage the consequences of fatigue. Discussion Experiences of chronic fatigue have patterns and personal meanings that vary between individuals. Caring for persons experiencing chronic fatigue requires acknowledgment of unique personal experiences and coping strategies. Due to the nature of the method, the results of this study are not generalizable and only reflect the experiences of the participants.